Pengaruh Reading Guide terhadap Hasil Belajar Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMPN 10 Lhokseumawe - Safitri, Maya (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
The low student learning outcomes in concentrating on reading long texts in Islamic Religious Education and Moral Education lessons result in students becoming bored and lacking focus. Researchers chose reading guides to be one of the methods in the learning process of Islamic Religious Education and Character. The purpose of this study was to determine whether or not there was an influence of reading guides on student learning outcomes in Islamic Religious Education subjects in class VIII SMP Negeri Lhokseumawe. This study uses a quantitative approach to the type of experimental research. Data collection techniques using tests and documentation. The sample selection was carried out using a purposive technique. The collected research data were analyzed using statistical methods. The research results obtained are the results of the initial ability test (pretest), the average value produced is 63.7. After being given treatment (treatment) and the final test (posttest) the average value rose to 82.4. Then the results of hypothesis testing using paired t-test obtained a significant value of -36,090. Because a significant value <0.05 indicates a significant difference between pretest and posttest. In this case, it shows that there is a significant influence on the treatment that has been given. Thus there is an influence from the Reading Guide method on student learning outcomes in PAI subjects at SMP Negeri 10 Lhokseumawe.